A system analysis of the development strategy of iron ore in China. (June 2016) - Wu, Jinxi; Yang, Jie; Ma, Linwei; Li, Zheng; Shen, Xuesi
Abstract: This paper aims to present a full picture of the current status and future trends of China's iron ore development using system analysis on the iron supply chain. First, we map China's iron flow to present the physical patterns of iron ore supply and demand in China. Next, the historical and future trends of iron ore development in China are discussed from four aspects including demand, resource availability, technology improvement, and strategy and policy. Based on these aspects, we conclude how to sustainably obtain overseas iron ore resources at a reasonable price as the key issue, and this issue is further analyzed from perspectives of market structure, the pricing mechanism, and Chinese steel companies' behavior. In conclusion, we determined China must enhance cooperation with the main global suppliers, expand overseas investments effectively, and enhance domestic coordination to secure the import of resources and reduce price fluctuations. Highlights: A Sankey diagram to reveal iron flows of China from crude ores to steel products. A system analysis of China's development strategy of iron ore. A discussion of the key issue of iron ore import to China from various perspectives.